Antibiotic resistance pattern of fish bacteria from freshwater and marine sources in Andamans - Shome, Rajeshwari; Shome, B R (Indian Journal of Fisheries, 2011)
Out of 326 total bacterial isolates from infected freshwater and marine fisheshaving no history of either prophylactic or therapeutic use of antibiotics, 145were identified atleast upto genus level. The predominanting genera wereAeromonas, Pseudomonas, Vibrio, Acinet,obacter, Enterobacter, Alcaligenes,Plesiomonas, Edwardsiella, Staphylococcus and Nocardia. In this study 88 ofthe identified bacteria belonging to 10 genera were tested for resistance patternagainst 26 different antibiotics by disc diffusion method in Muller-Hintor agar.The resistance level against streptomycin, penicillin and ampicillin wasexhibited by more than 60 per cent of the bacteria and oxytetracycline wasmost effective in commonly used tetracycline group of antibiotics. None of theisolates was sensitive to all the 26 antibiotics, whereas resistance in any singleisolate was found to be against a maximum of 14 antibiotics. Abundance ofnatural single and multiple antibiotic resistance was demonstrated to be uptothe upper limit of 3.7 and 97.1 % respectively. The situation appears to bealarming as this antibiotic resistance gene pool could be a potential threat tohumans and therefore is of public health significance.